28‐3: World's First 85‐in. 120Hz‐Driven 8K x 4K BCE IGZO GOA VA‐LCD. Issue 1 (30th May 2018) - Zhao, Ying-Chun; Zhao, Feng; Chang, CK; Chiu, Chung-Yi; Ray, Lin; Shi, Long-Qiang; Ge, Shi-Min; Kong, Zeng-Jie; Deng, Tong-Shuai; Xu, Feng-Cheng; Du, Peng
Abstract : We have developed a 85‐in. 120Hz‐Driven 8K4K VA‐LCD which succesfully applied BCE IGZO in GOA to gain super resolution, ultra ‐ high refresh rate for the first time in the world.